Growth of typha grass (Typha angustifolia) on gold-mine tailings with application of arbuscular mycorrhiza fungi - LULUK SETYANINGSIH; ARUM SEKAR WULANDARI; HAMIM HAMIM (Society for Indonesian Biodiversity, 2018)
Setyaningsih L, Wulandari AS, Hamim H. 2018. Growth of typha grass (Typha angustifolia) on gold-mine tailings with application of arbuscular mycorrhiza fungi. Biodiversitas 19: 504-509. Gold mine tailings contain extreme physical and chemical properties, which inhibit plant growth due to lower nutrition and higher heavy metal contaminants. Typha (Typha angustifolia) is type of grass growing well on waterlogged area including tailing dam. The objective of this study was to investigate the effect of arbuscular mycorrhizal fungi (AMF) in combination with compost and soil on the typha growth in gold mine tailings. The study was conducted in greenhouse by inoculating two AMF isolates (Glomus etunicatum and G. manihotis) to typha seedlings grown in pure tailing media, mixed tailing-compost media, and mixed tailing-compost-soil media. The compatibility and growth of typha grass were analysed after 1 month. Results showed that G. etunicatum and G. manihotis application significantly increased AMF colonization of typha roots up to 16.6% and 21.8% respectively. The length, number of leaves and biomass of typha also increased up to 90%, 50% and 97% respectively compared to those without AMF inoculation. G. etunicatum contributed the best growth of typha grown in mixed compost-soil-tailings, resulting in double increase of its length and biomass. The application of G. manihotis did not significantly increase the growth of typha in mixed media; however, under pure tailing, this mycorrhiza had the best induction for typha biomass and leaf number. In general, AMF application increased growth of typha grass in tailings media.